Antibiotic resistance pattern of bacterial isolatesfrom fishes of Andaman and Nicobar Islands - Sunder, Jai; Jeyakumar, S; Ahlawat, S P S; Rai, R B; Kundu, A; Senani, S; Chatterjee, R N; Saha, S K.,Yadav,S (Indian Journal of Fisheries, 2011)
A total of 131 bacteria were isolated from freshwater and marine fishes ofAndaman and Nicobar Islands. The percentage of Gram –ve bacteria were 88.52%,while Gram +ve bacteria were 11.47%. The predominating genera identified fromfresh water fishes were Aeromonas spp., Pseudomonas spp. and Yersinia spp.;while from marine fishes the predominating bacteria were Edwardsiella spp.and Aeromonas spp. The resistance pattern of Streptomycin, Cephalexin,Rifampicin and Nitrofurantoin were found to be more than 60% both by marineand fresh water bacterial isolates. A high degree of multiple drug resistancepatterns has been exhibited by the bacterial isolates from fishes, however theresistance pattern against antibiotics was more in marine bacteria. The highdegree of resistance to all the antibiotics by marine and fresh water bacteriamay pose a threat to human population by transferring these resistant genes toother bacteria as the consumption of fish food in these islands is very high.